Elevated Blood Pressure in Preterm-Born Offspring Associates With a Distinct Antiangiogenic State and Microvascular Abnormalities in Adult Life. - Lewandowski, A; Davis, E; Yu, G; Digby, J; Boardman, H; Whitworth, P; Singhal, A; Lucas, A; McCormick, K; Shore, A; Leeson, C (American Heart Association, 2014)
Preterm-born individuals have elevated blood pressure. We tested the hypothesis that this associates with an enhanced antiangiogenic circulating profile and that this association is mediated by variations in capillary density. We studied 204 adults aged 25 years (range, 20-30 years), of which 102 had been followed up prospectively since very preterm birth (mean gestational age, 30.3±2.5 weeks) and 102 were born term to uncomplicated pregnancies. A panel of circulating biomarkers, including soluble endoglin and soluble fms-like tyrosine kinase-1, were compared between groups and related to perinatal history and adult cardiovascular risk. Associations with cardiovascular phenotype were studied in 90 individuals who had undergone detailed assessment of microvascular, macrovascular, and cardiac structure and function. Preterm-born individuals had elevations in soluble endoglin (5.64±1.03 versus 4.06±0.85 ng/mL; P<0.001) and soluble fms-like tyrosine kinase-1 (88.1±19.0 versus 73.0±15.3 pg/mL; P<0.001) compared with term-born individuals, proportional to elevations in resting and ambulatory blood pressure, as well as degree of prematurity (P<0.05). Maternal hypertensive pregnancy disorder was associated with additional increases in soluble fms-like tyrosine kinase-1 (P=0.002). Other circulating biomarkers, including those of inflammation and endothelial activation, were not related to blood pressure. There was a specific graded association between soluble endoglin and degree of functional and structural capillary rarefaction (P=0.002 and P<0.001), and in multivariable analysis, there were capillary density-mediated associations between soluble endoglin and blood pressure. Preterm-born individuals exhibit an enhanced antiangiogenic state in adult life that is specifically related to elevations in blood pressure. The association seems to be mediated through capillary rarefaction and is independent of other cardiovascular structural and functional differences in the offspring.